Zircon fission-track (ZFT) single-grain data (Table S5) - Sarah Falkowski; Todd A Ehlers (PANGAEA, 2023)
This dataset contains 169 single-grain data for 11 samples acquired for zircon fission-track (ZFT) dating. ZFT data were acquired between 2020 and 2021 using the external detector and zeta-calibration techniques at the University of Tübingen, Germany.
In: Falkowski, S; Ehlers, TA (2023): Low-temperature thermochronometric data (AHe, AFT, ZHe, ZFT) from three bedrock sample transects across the eastern Central Andes, southern Peru [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.955437